What do Natural Categorization Studies tell us about the Concepts of Apes and Bears? - Jennifer Vonk; Moriah Galvan (Animal Behavior and Cognition, 2014)
To properly test hypotheses about the emergence of cognitive capacities in humans and other animals, it is important to test species that differ in morphology and ecology. One of the most notable aspects of animal ecology that has been championed as a factor in the evolution of cognitive skills is social complexity. However, to determine the significance of social lifestyle on an organism‟s cognitive abilities, it is important to test both social and less social species in similar tasks. We have conducted a series of natural categorization studies with three great ape species and recently extended this program of research to include American black bears (Ursus Americanus). Here we analyze the bears‟ choices of stimuli from our previously published categorization experiments and compare the pattern of their choices to that of apes tested previously. Like the apes, the individual bears show idiosyncratic choices that do not clearly differentiate between conceptual and perceptual strategies in performing categorization tasks. Despite their relatively asocial lifestyles, bears thus far appear to display cognitive abilities commiserate with those of the great apes. We suggest that researchers broaden their approach to study more diverse species in analogous tasks and make a concerted effort to view experimental tasks from the animals‟ perspectives.